Shoot Induction of Pandanus Tectorius through Shoot Culture in WPM Medium Supplemented With BAP And NAA - Matondang, Ikhsan; Effendi , Alvira Noer (Journal of Tropical Biodiversity, 2024)
The aim of this research is to determine the best shoot induction medium for Pandanus tectorius, a coastal plant valued for its ecological and economic benefits. Coastal degradation and land conversion have reduced its population, necessitating propagation efforts. In vitro culture was explored as a solution to address the scarcity of Pandanus tectorius. Woody Plant Medium (WPM) was prepared by combining 100 mL stock solution, 30 g sugar, and distilled water to 1 L, supplemented with 1 g activated charcoal, 0.1 g ascorbic acid, and plant growth regulators at varying concentrations. The pH was adjusted to 5.6–5.8, and agar was added before sterilization at 121 °C for 20 minutes. Explants consisting of 1 cm-long shoots were sterilized and cultured in bottles, with observations conducted over 8 weeks. Results showed that the best shoot induction was achieved using WPM supplemented with 5x10⁻⁶ M BAP and 5x10⁻⁶ M NAA, producing 1 to 3 shoots per explant. Data analysis using a factorial completely randomized design confirmed significant differences among treatments. This study demonstrates the effectiveness of in vitro propagation in restoring Pandanus tectorius populations and supports sustainable coastal management.